IMPLEMENTATION OF METHODE TREASURE HUNT TO IMPROVE THE COOPERATION OF STUDENT AND LEARNING OUTCOMES ( Studies in civic education Subjects in junior base school Bengkulu Utara) - Ari Sulastri; Wasidi Wasidi (UNIB Press, 2019)
The purpose this research describes the implementation of the methode treasure hunt, to improve the precision of student learning and achievement of learning on the subject of learning IPS 4th grade SD to Gugus II Bengkulu Utara, and to describe effective the implementation of methode treasure hunt in improving the cooperation and achievement 4th grade students of SD to Gugus II Bengkulu Utara, This research is a class action, combined with a quasi-experimental. The subjects were fourth grade SDN 014 Bengkulu Utara as PTK class and IVA SDN 002 Bengkulu Utara as the control class, and IVB SDN 002 Bengkulu Utara as an experimental class. Implementation procedures in Classroom Action Research, each cycle includes planning, action, observation and reflection. Data collection techniques use observation and test techniques in the form of evaluations given at the end of each cycle. In quansi research experiments, data collection techniques used test techniques. Based on the results of Classroom Action Research (PTK), in the first cycle the average value of student cooperation attained 59 with less criteria in the second cycle reaching 65 with good criteria, and increasing in the third cycle reached 82.3 with very good criteria. The results of the study of student learning achievement in the first cycle obtained the value of learning completeness 60%, cycle II 80% and cycle III 100%. In quansi research experiments, the results of the study showed a significant difference between the experimental class and the control class. This difference can be chosen from the results of the experimental class posttest score of 74.75 and the control class of 66.25. The results showed that the application of methode treasure hunt can increase their accuracy and observation learning achivement 4th grade students of SD to Gugus II Bengkulu Utara.